Memorable Tourism Experience Bibliometric Analysis: A Systematic Review - Juliana; Sabrina O Sihombing; Ferdi Antonio (Jurnal Mantik, 2022)
Creating unforgettable experiences is at the core of the tourism and hospitality industry. Improving the recall of consumption experiences can be used as a core marketing strategy in the experience economy. This study explores and analyses the relevance of keywords related to memorable tourism experiences in Scopus indexed scientific articles in 2018-2022. The research method used in this research is bibliometric and systematic analysis. Based on research conducted with bibliometric analysis of 155 keywords that are interconnected with one another related to Memorable Tourism Experience (MTE). The ten keywords with the most vital links were: unforgettable travel experience, intention to revisit, destination image, unforgettable travel experience, satisfaction, travel experience, coffee tour, heritage tourism, memory, and behavioural intention. This shows that these keywords are variables or topics often discussed in Scopus indexed scientific articles for the last five years. Analysis of the interrelationships between keywords includes tourism experience, one of which is carried out in tourist villages. Tourist villages are visited a lot because 1) there are unique attractions or attractions from the village itself, such as destination images and heritage tourism, and 2) there are facilities and accommodations such as lodging, eating and drinking facilities, hawker centres or souvenirs (culinary & coffee tourism). The) visitor centre, 3) there are tourist activities such as weaving, enjoying the scenery and others, 4) the existence of general development as an effort to create a tourist destination that provides the best service for tourists, From the pleasures and visits that have been made can create experiences memorable or meaningful, friendly and kind attitudes of residents towards tourists will also provide memory and affect the image of the destination. The purpose of doing tourism can be a determinant of the behaviour and return of tourists' intentions which can affect tourist destinations and the economy of residents.